LOCAL AND REGIONAL IDENTITIES IN THE CULTURAL SPACE OF POKUTTIA - Maykhrovych, Yurii (Ukrainian Cultural Studies, 2023)
This scientific article delves into the analysis of the intricate relationship between local and regional identity within the cultural milieu of Pokuttia. It sheds light on the processes of differentiation and identification that occur within this particular region. Notably, the understanding of the terms "local" and "regional" is contingent upon the scales of the spatial plane where these phenomena are juxtaposed within the realm of cultural geography. A pioneering interdisciplinary approach in cultural regional studies has brought forth a comprehensive examination of various cultural peculiarities specific to the Pokuttia region. These peculiarities encompass elements such as toponyms and the local language prevalent in the Pokuttian area, and their intricate interplay with other social aspects of the region's vibrant life. Through this multidisciplinary lens, a deeper understanding of the intricate tapestry of the region's cultural landscape has been attained. The essence of the discourse is the pivotal role that place assumes as the spatial foundation of local identity. Place emerges as a significant constituent imbued with its own set of symbolic, historical, and ideological attributes. It serves as a profound backdrop against which the nuances of local identity are shaped and expressed. Consequently, the profound interconnection between place and identity becomes a cornerstone for comprehending the complex dynamics within the Pokuttian cultural space. Moreover, this research affirms the inseparable link between local identity and the individual as the principal agent of spatial social reality. The individual, by infusing meaning into a particular place, distinguishes it as either "one's own" or "foreign." This dichotomy is primarily informed by a profound sense of uniqueness and a conscious choice in self-identification within the overarching global context. The interplay among place, individual, and society emerges as the fundamental constituents representing the fabric of local identity – an intricate construct encompassing both personal and collective consciousness within the broader paradigm of cultural space. The insights provided in this article offer valuable contributions to the understanding of the intricate interplay between local and regional identity within the unique cultural context of Pokuttia. Scholars and researchers in the fields of cultural studies, geography, and related disciplines will find these findings pertinent to their exploration of identity dynamics and cultural diversity in various regional contexts
Keywords: local identity; regional identity; space; Pokuttia; culture; society; individual; place